Pashtun Traditions versus Western Perceptions - Leo Karrer (Graduate Institute Publications, 2012)
Cross-cultural interactions take place every day in contemporary Afghanistan between locals and the thousands of foreigners working in the country as diplomats, officials from international organisations and humanitarian aid workers. As their work requires them to interact with Afghans in manifold ways, all foreigners are, at least indirectly, required to negotiate. Karrer's ePaper sheds light on the cross-cultural issues likely to contribute to the difficulties encountered by the internation...